English Language Learning-Based Open Space (ELLBOS) for young learners in the tourism area - Nehru Pasoloran Pongsapan; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2020)
This research aims to actualize the Tana Toraja district government program as an "English Speaking Area". This research also is subject to improve English communication skills for the young learners in Tana Toraja and produce English Language Learning-Based Open Space (ELLBOS) as a prototype of an English language teaching approach for young learners in the tourism area. The research applied the ADDIE research design consists of three cycles: preparation, implementation, and evaluation. This research found five issues: (1) participant reported that they are enthusiasm in English lessons; (2) the participants need to learn English; (3) the English-speaking skill is essential for students; (4) students revealed that are unhappy in learning English in the classroom; (5) students experienced peaceful learning atmosphere if learning English outside the classroom. This research recommends the significance of applying the English Language Learning-Based Open Space (ELLBOS) for young learners in the tourism area. It is good if the teacher does English learning outside the classroom with open space to feel free to explore their potency in learning English.